Temporal Changes in the Genetic Diversity of Plasmodium vivax Merozoite Surface Protein-1 in Myanmar - Haung Naw; Jung-Mi Kang; Mya Moe; Jinyoung Lee; Hương Giang Lê; Tuấn Cường Võ; Yi Yi Mya; Moe Kyaw Myint; Zaw Than Htun; Tong-Soo Kim; Ho-Joon Shin; Byoung-Kuk Na (Pathogens, 2021)
Despite a significant decline in the incidence of malaria in Myanmar recently, malaria is still an important public health concern in the country. Although Plasmodium falciparum is associated with the highest incidence of malaria in Myanmar, the proportion of P. vivax cases has shown a gradual increase in recent years. The genetic diversity of P. vivax merozoite surface protein-1 block 5-6 (pvmsp-1 ICB 5-6) in the P. vivax population of Myanmar was analyzed to obtain a comprehensive insight into its genetic heterogeneity and evolutionary history. High levels of genetic diversity of pvmsp-1 ICB 5-6 were identified in the P. vivax isolates collected from Myanmar between 2013 and 2015. Thirty-nine distinct haplotypes of pvmsp-1 ICB 5-6 (13 for Sal I type, 20 for recombinant type, and 6 for Belem type) were found at the amino acid level. Comparative analyses of the genetic diversity of pvmsp-1 ICB 5-6 sequences in the recent (2013–2015) and the past (2004) P. vivax populations in Myanmar revealed genetic expansion of the pvmsp-1 ICB 5-6 in recent years, albeit with a declined incidence. The recent increase in the genetic heterogeneity of Myanmar pvmsp-1 ICB 5-6 is attributed to a combination of factors, including accumulated mutations and recombination. These results suggest that the size of the P. vivax population in Myanmar is sufficient to enable the generation and maintenance of genetic diversity, warranting continuous molecular surveillance of genetic variation in Myanmar P. vivax.